A retrospective analysis from NHANES 2003-2018 on the associations between inflammatory markers and coronary artery disease, all-cause mortality and cardiovascular mortality. - Tong Sun; Penglei Chen; Xuwei Zheng (PLoS ONE, 2025)
Background The objective of this research was to investigate the associations between inflammation markers and coronary artery disease (CAD), along with all-cause mortality and cardiovascular mortality. Methods This study utilized data from the National Health and Nutrition Examination Survey (NHANES) collected between 2003 and 2018. The platelet-to-lymphocyte ratio (PLR), neutrophil-to-lymphocyte ratio (NLR), monocyte-to-lymphocyte ratio (MLR), and systemic immune inflammation index (SII) were calculated based on blood test results. The diagnosis of CAD was obtained from self-reported cardiovascular health questionnaires. Participants' survival status was sourced from the National Death Index (NDI) of the National Center for Health Statistics (NCHS). Logistic and Cox regression models were employed to investigate the associations between PLR, NLR, MLR, and SII with CAD, all-cause mortality, and cardiovascular mortality. Results A total of 32,683 individuals from the 2003-2018 NHANES were involved. After adjusting for potential confounders, each 1-unit increase in log (NLR) and log (MLR) was associated with a 29% (95% CI: 1.15-1.46, P < 0.001) and 67% (95% CI: 1.40-1.99, P < 0.001) increase in the risk of CAD, respectively. Notably, when log (PLR) exceeded 4.93(PLR = 138.38) and log (SII) surpassed 6.11(SII = 450.34), the risk of CAD increased sharply (P < 0.001). Furthermore, individuals in the highest quartiles (Q4) of PLR, NLR, MLR, and SII had significantly higher risks of all-cause mortality (13%, 88%, 91%, and 42%, respectively) and cardiovascular mortality (48%, 194%, 139%, and 90%, respectively) compared to those in the lowest quartile (Q1), with all P-values <0.001. Moreover, MLR had the highest the area under the curve (AUC) value (AUC:0.642, 95% CI: 0.629-0.654), followed by NLR (AUC:0.600, 95% CI: 0.587-0.612) for distinguishing CAD. Conclusion In this study, we found that PLR, NLR, MLR, and SII were associated with increased prevalence of CAD, as well as increased risks of all-cause and cardiovascular mortality. These inflammatory markers may serve as valuable clinical indicators for CAD, all-cause and cardiovascular mortality in the general population.